Show that tan 3x tan 2x tan x = tan 3x – tan 2x – tan x.​

Question

Show that tan 3x tan 2x tan x = tan 3x – tan 2x – tan x.​

in progress 0
Katherine 1 month 2021-09-22T00:29:03+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-22T00:30:29+00:00

    Let 3x = 2x + x

    Taking “tan” on both sides,

    tan 3x = tan (2x + x)

    We know that,

    Class 11 Chapter 3 Imp Ques 5 figure 1

    tan 3x = (tan 2x + tan x)/ (1- tan 2x tan x)

    tan 3x(1 – tan 2x tan x) = tan 2x + tan x

    tan 3x – tan 3x tan 2x tan x = tan 2x + tan x

    tan 3x – (tan 2x + tan x) = tan 3x tan 2x tan x

    Therefore, tan 3x – tan 2x – tan x = tan 3x tan 2x tan x.

    0
    2021-09-22T00:30:45+00:00

    Answer:

    727

    Step-by-step explanation:

    • please mark as brain list and follow me

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )